A Case Report: Diabetic Ketoacidosis in Patient with type 1 Diabetes Mellitus with Complication Septic Shock and AKI Stage III on HD Triggered by Perianal Abscess - Muhammad Ikhsan Kartawinata; Yusni Puspita (Journal of Anesthesiology and Clinical Research, 2020)
Introduction. Diabetic ketoacidosis (DKA) is an acute, life-threatening complication in diabetes mellitus. Infection is a common precipitating cause of diabetic ketoacidosis (DKA) in known diabetic patient, and diabetic ketoacidosis (DKA) often presents as the first symptom of an undiagnosed diabetes. diabetic ketoacidosis (DKA) is diagnosed with combination of hyperglicaemia, acidosis metabolic and ketonuria. Case Presentation. A 27 years old male patient, admitted to Intensive Care Unit with decrease level of consciousness (GCS 3), he was intubated and present with respiratory distress, metabolic acidosis, high glucose level, ketonuria with renal failure as a target organ. Patient known has perianal abscess as a triggered of diabetic ketoacidosis (DKA), turn into septic shock and underwent debridement surgery to source control the infection. The patient was treated in intensive care unit for 9 days, and sent to ward with GCS 15 an no sequelae of organ failure. The treatment of diabetic ketoacidosis (DKA) should include correcting the often substantial hypovolemia, the hyperglycemia, electrolyte imbalance and the triggering factor of diabetic ketoacidosis (DKA). Conclusion. Prompt surgical intervention, antibacterial therapy, rapid restoration of glycemic control are crucial to prevent mortality in diabetes mellitus patients complicated with abscess.